2022
DOI: 10.53730/ijhs.v6ns4.5525
|View full text |Cite
|
Sign up to set email alerts
|

association between body mass index and cardiovascular-related mortality

Abstract: The relationship between body mass index (BMI) and cardiovascular (CVD) related mortality has been extensively investigated in the general population. However, the research on this matter is relatively limited, and the conclusions from these studies are inconsistent. This study aimed to review the association between body mass index with CVD related mortality. Articles that reported hazard ratio (HR) for all-cause mortality using standard BMI categories of general populations of adults were selected from the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The average gestational age of mothers with Covid-19 at delivery is the third trimester. The current research is in accordance with what was stated by previous researchers which stated that pregnant women who are infected with covid-19 have a 1.33 times higher risk of giving birth normally compared to pregnant women who are not infected (Widiyanto, Atmojo, Livana, Fajriah, Putri , Nahak, & Anulus, 2021). The gestational age when the mother was infected with covid-19 ranged from 29-41 weeks' gestation, with an average gestational age of 37.5 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…The average gestational age of mothers with Covid-19 at delivery is the third trimester. The current research is in accordance with what was stated by previous researchers which stated that pregnant women who are infected with covid-19 have a 1.33 times higher risk of giving birth normally compared to pregnant women who are not infected (Widiyanto, Atmojo, Livana, Fajriah, Putri , Nahak, & Anulus, 2021). The gestational age when the mother was infected with covid-19 ranged from 29-41 weeks' gestation, with an average gestational age of 37.5 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…This study aimed to investigate factors that influenced patients satisfaction in regarding the services of community health care (Widiyanto, 2022). Our study showed that there is association between accreditation status and health insurance with patients satisfaction on community health care services.…”
Section: Discussionmentioning
confidence: 97%
“…In many areas in Indonesia, often times, facilities for the pedestrian are used by the street vendors (Busthanul et al, 2020). On the other hand, buildings are designed with stairs that are farther from the entrance causing people to choose elevator instead (Yeung and Johnston, 2020;Widiyanto 2022)).…”
Section: Discussionmentioning
confidence: 99%